The Diseconomiies of Using the Policy Instruments to Control Inflation and in Particular Credit Growth in Beijing and Shanghai: Eviidence on Shadow Banking - Hovnanian, Serge (Université d'Ottawa | University of Ottawa, 2014)
The increasing credit growth is a source of deep concern to the Chinese economy and containing it has become the upmost priority for the People’s Bank of China (PBC) The two main tools used by the Chinese authorities to control the liquidity, the credit growth and inflation are the reserve requirement ratio (RRR) and the policy interest rate. This paper’s objective is to study the effectiveness of these policy changes in controlling inflation and in particular credit growth. Due to t he important macroeconomic differences among Chinese cities, the paper will focus on two main cities:Beijing and Shanghai. The results show that the two policy tools are effective at containing the overall inflation in China However when it comes to credit growth containment, the results show that the use of the reserve requirement ratio tool is ineffective because itincreases credit growth instead of contracting it.